von Willebrand's disease: an important cause of dysfunctional uterine bleeding - Woo, Y.L.; White, B.; Corbally, R.; Byrne, M.; O'Connell, N.; O'Shea, E.; Sheppard, B.L.; Bonnar, J.; Smith, O.P. (Lippincott, Williams & Wilkins, 2002)
We assessed the prevalence of von Willebrand's disease (VWD) in patients with objectively confirmed dysfunctional uterine bleeding. A case–control study was designed to include 38 patients with objectively confirmed dysfunctional uterine bleeding and 38 age-matched controls with normal menstrual blood loss (MBL). Menorrhagia was defined as a mean MBL of greater than 80 ml on three consecutive menses as measured by the alkali haematin method. von Willebrand factor antigen, von Willebrand factor activity (VWF:Ac) and factor VIII:C were measured on three serial venous blood samples 1 week apart. VWD was diagnosed in five of 38 (13%) patients with menorrhagia and one of 38 (2.6%) patients with normal menstrual blood loss. The mean VWF:Ac value was significantly reduced in patients with menorrhagia (mean ± standard deviation, 84.5 ± 26.7 IU/dl versus 103.9 ± 34.5 IU/dl;P < 0.01) and this effect persisted after exclusion of patients diagnosed with VWD. Failure to investigate patients for VWD will limit the potential benefits of medical therapies such as tranexamic acid or nasal desmopressin [1-desamino-8-D-arginine vasopressin, (DDAVP)] and, in addition, will lead to an increased risk associated with surgical intervention in patients with undiagnosed VWD.